A Qualitative and Literature-Based Technology Study of Drilling Rig Hoisting System Equipment - Rachmasari Pramita Wardhani; Cristo Nathanael Rayhan Simanjuntak; Abdul Gafar Karim (Scientific Journal of Engineering Research, 2026)
Oil and gas energy in Indonesia plays a vital role in driving the country's economy, particularly as a foreign exchange earner and domestic energy supplier. The hoisting system is located on the surface of the rig and works in conjunction with other drilling systems. This study aims to provide an introduction and understanding of the equipment used in hoisting systems in oil and gas drilling activities, enabling students to understand the types of equipment and their uses. This relates to the drilling equipment course, which aims to provide students with a better understanding of the context of practical learning, which is difficult to conduct in the field for direct observation. Therefore, the research method used is a literature review with a qualitative approach to narrate and describe the process of activities carried out in practical learning, starting from the equipment introduction stage, gathering technical information from literature studies, and observing the drilling equipment using sketches and instructional videos of the equipment used in the drilling hoisting system. Based on these observations, students are able to explain and understand the scope of the hoisting system in oil and gas drilling.